Exploring the potential mechanism of Fritiliariae Irrhosae Bulbus on ischemic stroke based on network pharmacology and experimental validation - Zijie, Wang; Anan, Jiang; Hongmei, Xiao; Xiaofan, Yuan; Shaoru, Zhang; Xinyue, Qin (Frontiers in Pharmacology, 2022)
Objective: To study the potential targets and molecular mechanisms of Fritiliariae Irrhosae Bulbus (FIB) in the treatment of ischemic strokes based on a network pharmacology strategy, combined with molecular docking and animal experiments. Methods: The active components and targets of FIB were screened by TCMSP and TCMIP database, and the related targets of ischemic strokes were screened by GeneCards, OMIM, CTD and DrugBank. The protein interaction network was constructed by STRING, the PPI network diagram was drawn by using Cytoscape software, and the key targets of FIB treatment of ischemic strokes were analyzed by MCODE. The DAVID database was used for GO and KEGG enrichment analysis, and the potential pathway of FIB against ischemic strokes was obtained. Molecular docking is performed through AutoDock Tools 1.5.6 software. Finally, a mouse model of ischemic stroke was established, and the results of network pharmacology were verified by in vivo experiments. Realtime Polymerase Chain Reaction and Western blot was used to detect the expression levels of related targets in mouse brain tissue. Results: 13 kinds of active components of FIB were screened, 31 targets were found in the intersection of FIB and ischemic strokes, 10 key targets were obtained by MCODE analysis, 236 biological processes were involved in GO enrichment analysis, and key targets of KEGG enrichment analysis were mainly concentrated in Neuroactive light receptor interaction, Calcium signaling pathway, Cholinergic synapse, Hepatitis B, Apoptosis - multiple specifications Pathways in cancer and other significantly related pathways. Molecular docking showed that the main active components screened had good binding activity with target proteins. Animal experiments showed that the infarct volume of brain tissue in the FIB treatment group was significantly reduced. RT qPCR and Western Blot results showed that FIB could inhibit the expression of active-Caspase3, HSP90AA1, phosphorylated C-JUN and COX2. Conclusion: Based on network pharmacology, the effect of FIB in the treatment of ischemic strokes through multi-component-multi-target-multi-pathway was explored. The therapeutic effect and potential mechanism of FIB on ischemic strokes were preliminarily explored, which provided a certain basis for further research on the pharmacodynamic material basis, mechanism of action and clinical application.